Aplicación de la tecnología de atmósfera controlada para la conservación de la granadilla - Orjuela Castro, Javier Arturo; Pinilla Ortiz, Adielht Lucero; Rincón Murcia, José Rafael (Ingeniería, 2001)
Colombia has a great number of varieties of fruits, the level of exports to Europe has come increasing contributing significantly to improve its trade balance. To maintain the level of competitiveness that places Colombia in the first place among the exporters of the world market of the maypops, it is necessary to improve and to maintain the quality of the fruit. The maypops (Passiflora Ligularis Juss) it is a tropical fruit that has excellent characteristic nutritional and a high consumption in fresh state (comparative advantage). The purpose of this investigation was to retard the process of maturation of the fruits of the maypops by means of the Technology of Controlled Atmosphere. For such an end was combined mixtures with percentages of 3 and 6% of O2 with 3 and 6% of CO2, a refrigerated witness and a witness to the environment a total of 14 observation units. Fruits coming from the same lot were selected, they were classified in the grade 4 of maturation, according to letter of colors, and of them they took samples of 1 Kg to pack them in previously disinfected chambers. The utilized chambers were glass containers to those that were conditioned plugs and two valves of to inject and to control the composition of the mixtures, previously the estanqueidad of the gases was proven. During 20 days, every 24 hours the composition of each mixture was analyzed a similar to the inicial mixture. At the end of the experimentation, was opposing that the subjected fruits to the atmospheres retarded their maturation. When carrying out variance analysis, of the breathing quotient and of the index of maturity, ace well ace the tasting panel was confirmed that the atmosphere composed by 6% of O2, 6% of CO2 and 88% of N2, presented the best behavior. This way it is demonstrated that this technology is an alternative been worth to solve the problem of marketing of the maypops, because the country only exports at the present time 2% of the total of its production.